IMPLIED MEANINGS OF FLOUTING OF MAXIMS IN MATA NAJWA TALK-SHOW PROGRAM PENEBAR INSPIRASI EPISODE - KHAKIM, MUHAMAD LUKMAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Cooperative Principle, Flouting of Maxim, Implied MeaningHuman is a social creature who has a need to socialize with others. In order to be able to do so, human needs to communicate well. Good communication needs a good understanding between the speaker and the listener in which they understand what each other means. Cooperative principle is a principle which can help the speaker and the listener to understand what each other means. However, sometimes the message given by the speaker contains not only literal meaning but also implied meaning. In a communication, though, the speaker sometimes does not fulfill the principle. When the speaker intentionally disobeys the principle, it means that the speaker flouts the maxim. The writer conducted the study of implied meaning in Mata Najwa talk-show program. Hence, in this study the writer answered problems of the study, namely: (1) What maxims are flouted as shown in the translated version of the host and the guests’ utterances produced by the host and the guests in Mata Najwa talk-show program Penebar Inspirasi episode, and (2) What are the implied meanings of flouting of maxims produced by the host and the guests in Mata Najwa talk-show program Penebar Inspirasi episode. This study employs qualitative approach to describe the implied meaning behind the host and the guests’ utterances of the flouting of maxims.The findings of this study showed that there were four maxims that were flouted by the host and the guests, namely: (1) maxim of quality, (2) maxim of quantity, (3) maxim of relevance, and (4) maxim of manner. Also, they flouted the maxim because of certain reasons. At a time, they want to make some points where they want the listener to understand it, while in the other hand, they wanted to avoid talking about certain topic and giving certain information that they did not want to tell.Hence, the writer suggests the next researcher to analyze the flouting of maxim in different objects and to use other theory that will help to define the implied meaning.